Occurrence of Pneumococcal Meningitis in Iraq (Baghdad Science Journal, 2012)
This study focuses on the relative frequency of Streptococcus pneumoniae in children with culture-proven bacterial meningitis. The epidemiology has been investigated with clinical and laboratory findings in The Central Public Health Laboratory, Iraq from April to September, 2010. From (138) samples , (55) cases (39.85 %) were diagnosed by physician as bacterial meningitis, (23) cases (16.66 %) as viral menginitis , (18) cases (13.04 %) as different medical cases (e.g febrile convulsion , meningoencephalitis , epilepsy …etc) and (42) cases (30.43 %) as unidentified medical cases. For bacterial meningitis S.pneumoniae was isolated from (10) cases (18.18 %) only. The median age for bacterial meningitis was (130.75) month and the predominance was in the age group (1-20) months which appear as (42) cases (76.36 %) . Fever was the frequent presenting symptoms in (49) cases (89.09 %) , followed vomiting in (34) cases (61.81 %) , then irritability and seizures in (29 ,25) cases (52.72 , 45.45) % respectively . In bacterial meningitis , the mean for glucose and protein levels was (44 and 65) (mg/dl) respectively.